Dragonfire - Grant, Donna (Grant, Donna. Dark kings novel, 2018)
As a Dragon King, Roman is sworn to protect all mortals<U+2015>even though they no longer believe in dragons. But deep in the Carpathian Mountains, he discovers a beautiful and mysterious gypsy who possesses the power to see into his very soul. To reignite the fire in his heart. And to help him find the long-lost sword that could save the dragons forever<U+2026> Sabina remembers the stories her grandmother told her. Legends of dragons and kings, fire and ice. And she<U+2019>s never forgotten the dark prophecy that filled her ancestors with fear<U+2015>a fate they tried to prevent by stealing a Dragon King<U+2019>s sword. Sabina knows that helping Roman is dangerous. He is a dragon betrayed, and more powerful than any man. He could destroy her in a single fiery embrace. But how can she resist the longing in his eyes<U+2015>or the feelings in her heart<U+2015>when their destinies are bound by desire?